Application of a long-range swept source optical coherence tomography-based scheme for dimensional characterization of multilayer transparent objects - Morel, Eneas Nicolas (2017)
This work presents the use of a recently developed interferometric system based on the sweptsource optical coherence tomography (SS-OCT) technique, which allows the characterization of transparentand semitransparent multilayer systems employing a tunable fiber-optic laser with a coherence length suitablefor achieving long-deep range imaging (>10 cm). The inclusion of fiber Bragg gratings in the system allows it toperform a self-calibration in each sweep of the light source. Measurements carried out on cuvettes, ampoules,small bottles, and glass containers used in the pharmaceutical industry are presented. The thicknesses of thewalls and the distance between them were determined. Transparent and semitransparent objects of a multilayertype of different thicknesses were also measured. The configuration presented allows extension of the measurementrange obtainable with the usual OCT systems, demonstrating the potentiality of the proposed scheme tocarry out quality control in industrial application.